PERAN EDUCATOR PERAWAT DENGAN PELAKSANAAN DISCHARGE PLANNING PADA PASIEN DI RUANG TULIP 1C RSUD ULIN BANJARMASIN - Pertiwiwati, Endang; Rizany, Ichsan (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2016)
Discharge planning is the interaction and collaboration among of health care workers, patients,and families together to provide and arrange the necessary continuity of patient care. During theimplementation of discharge planning, nurses play a role in education to the patient and familyfor prepare the return and the possible need for follow-up care at home. This study aimed todetermined the relationship of the educator nurse’s role with the implementation of dischargeplanning for patients in Tulip 1C RSUD Ulin Banjarmasin. The study design was observationalanalytic cross sectional using saturated sampling and the subjects were 29 respondents. The roleof a good educator were 17 people (59%) and the implementation of good discharge planningwere 18 people (62%). Data analysis using Chi Square test with the results obtained p = 0.002,which means p <0.05, so it can be concluded that there was a significant relationship between thenurse educator role with the implementation of discharge planning for patients in Tulip 1C RSUDUlin Banjarmasin.